VOLUMETRIC PROPERTIES AND VISCOSITY OF DIETHYL SULFOXIDE IN ACETONITRILE AT DIFFERENT TEMPERATURES (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
Densities and viscosities of diethyl sulfoxide–acetonitrile binary mixtures have been measured over the full range of compositions at temperatures from 298.15 to 323.15 K. Excess molar volumes, apparent molar volumes, partial molar volumes, excess partial molar volumes, partial molar volumes at infinite dilution and thermal expansion coefficients for binary liquid mixtures were calculated. The excess molar volumes are negative over the whole range of composition and become more negative with increasing temperatures from 298.15 to 323.15 K. Viscosity deviations and excess Gibbs energy of viscous flow activation were calculated. The viscosity deviations are negative, but contrary to the excess molar volumes deviations in viscosity become less negative with increasing temperatures. The excess molar volumes and viscosity deviations were correlated by Redlich–Kister equation. Results are discussed in terms of molecular interactions and molecular size and shape in these binary mixtures. The obtained results were interpreted on the basis of dipole-dipole interaction between polar groups of diethyl sulfoxide and acetonitrile.
Keywords: DMSO, volumetric properties, viscosity, intermolecular interactions